2018
DOI: 10.15283/ijsc17077
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Umbilical Cord-derived Mesenchymal Stem Cell Transplantation in a Patient with Cerebral Palsy: A Case Report

Abstract: BackgroundCerebral Palsy (CP) is the most common motor disability reason of childhood that occurs secondarily to non-progressive damage in the brain whose development is still ongoing.Methods6-year-old dystonic-spastic male CP patient received allogenic mesenchymal stem cells treatment four times as 1×106/kg in intrathecal and intravenous administration of Umbilical Cord-derived mesenchymal stem cells (UC-MSCs) ways. Before and after the treatment, the patient was followed-up with FIM (Functional Independent M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…The improvements were likely related to the anti-inflammatory potential of hUC-MSCs since IL-1α, IL-6, and TNF-β were decreased significantly after transplantation [46]. When considering the transplantation route of cell therapy, intravenous administration was preferred to intrathecal injection for better compliance, since pain at the injection site was a complaint due to intrathecal administration [16]. In addition, hUC-MSCs were given at dosages of 4.5~5.5 × 10 7 cells intravenously in our study, which was supported by the suggested doses in the Clinical Cell Therapy Guidelines for Neurorestoration [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvements were likely related to the anti-inflammatory potential of hUC-MSCs since IL-1α, IL-6, and TNF-β were decreased significantly after transplantation [46]. When considering the transplantation route of cell therapy, intravenous administration was preferred to intrathecal injection for better compliance, since pain at the injection site was a complaint due to intrathecal administration [16]. In addition, hUC-MSCs were given at dosages of 4.5~5.5 × 10 7 cells intravenously in our study, which was supported by the suggested doses in the Clinical Cell Therapy Guidelines for Neurorestoration [47].…”
Section: Discussionmentioning
confidence: 99%
“…Functional improvements with alleviation of brain lesions were detected after hUC-MSC transplantation in a series of animal model studies [13][14][15]. In clinical case reports, gross motor and cognitive functions were improved after hUC-MSC [16] and bone marrow mononuclear cell transplantation [17]. In addition, gross motor function classification scores were promoted significantly after human embryonic stem cell treatment in a retrospective cohort analysis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Umbilical cord tissuederived MSCs, which were manufactured under cGMP (current Good Manufacturing Practice) conditions (LivMedCellIstanbul, Turkey) were used in this study. Cell preparation steps were performed according to cGMP requirements as described previously (11,12). The cells were characterized by identifying the potential for differentiation using a fl ow cytometer and immunohistochemical analysis, cell aging, cell cycle, annexin V/PI and telomerase enzyme activity at the third passage.…”
Section: Methodsmentioning
confidence: 99%
“…(2016) [54] Spinal cord injury AD 14 41.9 (20–66) IT 9 × 10 7 cells at 1-month interval 2 Motor (5/14) and sensory (10/14) functional recovery after 8 months Nausea, vomit, head ache Okur SC et al. (2018) [64] Cerebral palsy UC 1 6 IT 1 × 10 6 /kg 4 Motor functional recovery after 18 months Back pain IV 1 × 10 6 /kg Wang et al. (2015) [15] Cerebral palsy UC 16 (8 twins) 6.29 (3–12) IT 1–1.5 × 10 7 cells at 3–5 days interval 4 Motor functional recovery after 1 & 6 months No Cheng H et al.…”
Section: Clinical Application Of Mscs For Neurological Disordersmentioning
confidence: 99%